1914
DOI: 10.1021/ja02186a017
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Bacterial Metabolism.

Abstract: A. I. KENDALL, A. A. DAY AND A. W. WALKER. (4) B. pyocyaneus is less proteolytic in cream than it is in whole milk or skimmed milk. (5) The presence of certain pathological bacteria, B. typhosus, and B. paratyphosus alpha and beta, cannot be detected in milk by the chemical changes which they induce in it. CHICAOO. ILL. [FROM THE DEPARTMENT OF BACTERIOLOGY, NORTHWESTERN UNIVERSITY MEDICAL SCHOOL. ] STUDIES IN BACTERIAL METABOLISM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1917
1917
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In contrast the increase in ammonia-plus-urea nitrogen when glucose was not added to saliva was 200-300%. Some years ago Kendall and Farmer (8) observed that bacteria of a number of different types growing in cultures of various compositions produced more ammonia in the absence of, than in the presence of, glucose. Our findings with respect to glucose are of a similar sort.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast the increase in ammonia-plus-urea nitrogen when glucose was not added to saliva was 200-300%. Some years ago Kendall and Farmer (8) observed that bacteria of a number of different types growing in cultures of various compositions produced more ammonia in the absence of, than in the presence of, glucose. Our findings with respect to glucose are of a similar sort.…”
Section: Resultsmentioning
confidence: 99%
“…21,25] in an apparatus [I8] developed for use with reactive substances. The measured triple points, i n degrees Celcius (9), and calculated purities, in mole percent, for fractions A, B, C , and D were, respectively: ["I and 9.7OC [14]. The purest acid obtained by distillation alone was about 99 mole percent.…”
Section: Dichloroucetic Acidmentioning
confidence: 94%
“…Kendall and his co-workers, taking the production of ammonia as a criterion of proteolysis, usually found a decrease in the presence of a carbohydrate. Kendall, Day and Walker (1922) found that glucose increased the total amino nitrogen in cultures of three strains of Clostridium botulinum, but caused a decrease in cultures of three other strains. DeBord (1923) with a variety of organisms found that glucose increased the amino-N and decreased the ammonia-N. An examination of the graphs in this latter publication, however, shows that even though the conclusions drawn are valid as the culture ages up to ten days, in some instances the events taking place in the first 24 to 48 hours are not so simple, the curves frequently transacting each other.…”
Section: Protein Sparingmentioning
confidence: 94%